Lung cancer that recurred as carcinoma en cuirasse. Issue 11 (5th October 2022) - Nozu, Shohei; Nakanishi, Norihiko; Sadamoto, Yasushi; Sugita, Atsuro
Key message: Cutaneous metastasis from lung cancer is rare. We report an unusual cutaneous metastasis known as "carcinoma en cuirasse" 7 years after left upper lobectomy to treat an adenocarcinoma of the lung. Abstract : We report an unusual cutaneous metastasis known as "carcinoma en cuirasse" 7 years after left upper lobectomy to treat an adenocarcinoma of the lung.